Comparison of composite measures of disease activity in an early seropositive rheumatoid arthritis cohort. Issue 12 (1st May 2007) - Ranganath, Veena K; Yoon, Jeonglim; Khanna, Dinesh; Park, Grace S; Furst, Daniel E; Elashoff, David A; Jawaheer, Damini; Sharp, John T; Gold, Richard H; Keystone, Edward C; Paulus, Harold E
Abstract : Objective: To evaluate concordance and agreement of the original DAS44/ESR-4 item composite disease activity status measure with nine simpler derivatives when classifying patient responses by European League of Associations for Rheumatology (EULAR) criteria, using an early rheumatoid factor positive (RF+) rheumatoid arthritis (RA) patient cohort. Methods: Disease-modifying anti-rheumatic drug-naïve RF+ patients (n = 223; mean duration of symptoms, 6 months) were categorised as ACR none/20/50/70 responders. One-way analysis of variance and two-sample t tests were used to investigate the relationship between the ACR response groups and each composite measure. EULAR reached/change cut-point scores were calculated for each composite measure. EULAR (good/moderate/none) responses for each composite measure and the degree of agreement with the DAS44/ESR-4 item were calculated for 203 patients. Results: Patients were mostly female (78%) with moderate to high disease activity. A centile-based nomogram compared equivalent composite measure scores. Changes from baseline in the composite measures in patients with ACRnone were significantly less than those of ACR20/50/70 responders, and those for ACR50 were significantly different from those for ACR70. EULAR reached/change cut-point scores for our cohort were similar to published cut-points. When compared with the DAS44/ESR-4 item, EULAR (good/moderate/none) percentage agreements were 92 with the DAS44/ESR-3 item, 74 with the Clinical Disease Activity Index, and 80 with the DAS28/ESR-4 item, the DAS28/CRP-4 item and the Simplified Disease Activity Index. Conclusion: The relationships of nine different RA composite measures against the DAS44/ESR-4 item when applied to a cohort of seropositive patients with early RA are described. Each of these simplified status and response measures could be useful in assessing patients with RA, but the specific measure selected should be pre-specified and described for each study.